A critical review on the development of wax inhibiting agent in facilitating remediation process of contaminated groundwater - Alpandi, A.H. (Springer Science and Business Media Deutschland GmbH, 2021)
Transportation of crude oil and refined petroleum is the main function of pipeline system in petroleum industry. Unfortunately, wax precipitation has become a serious problem for the petroleum industry where it causes pipeline blockage and eventually results in operational catastrophe. Up-to-date, the technique used to mitigate wax deposition by injecting chemical wax inhibiting agent remains a debate amongst researchers. This review addresses the evolution of chemical wax inhibitor generations started from polymer-based in the early 1980s, followed by biosurfactant-based in the late 1990s and finally plant-based or agricultural-based in recent years. Pivoting to environmental impact, petroleum industry is amidst finding a green wax inhibiting agent to solve wax deposition problem that occurs during the transportation of crude oil whilst facilitating the remediation process of contaminated groundwater. Â© 2021, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.